Textiles in motion : dress for dance in the ancient world - Gouy, Audrey (Oxbow Books, 2023)
"An innovative series of case studies looking at the significance, meaning and social context of costume and textiles used in dance among a variety of ancient cultures and civilisations"-- Provided by publisher.
Keywords: Textile fabrics, Ancient.; Dance costume -- History.; Clothing and dress -- History -- To 500.; Dance -- History.; Dance -- Social aspects.; Danse -- Histoire.; Textiles et tissus antiques.; Danse -- Aspect social.; Costumes de danse -- Histoire.; SOCIAL SCIENCE / Archaeology; Clothing and dress; Dance; Dance -- Social aspects; Textile fabrics, Ancient; To 500; History